2013
DOI: 10.1186/1750-1172-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive spastic ataxia of Charlevoix Saguenay (ARSACS): expanding the genetic, clinical and imaging spectrum

Abstract: BackgroundMutations in SACS, leading to autosomal-recessive spastic ataxia of Charlevoix-Saguenay (ARSACS), have been identified as a frequent cause of recessive early-onset ataxia around the world. Here we aimed to enlarge the spectrum of SACS mutations outside Quebec, to establish the pathogenicity of novel variants, and to expand the clinical and imaging phenotype.MethodsSequencing of SACS in 22 patients with unexplained early-onset ataxia, assessment of novel SACS variants in 3.500 European control chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
179
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 25 publications
4
179
1
Order By: Relevance
“…Autosomal Recessive Spastic Ataxia of Charlevoix Saguenay (ARSACS) (OMIM phenotype #270550) shows a challenging phenotypic overlap with HSP and HA, with a remarkable clinical diversity. [20][21][22] ALS2 (Alsin) (OMIM gene *606352) is another prominent example of a gene implicated in pyramidal syndromes, with overlapping roles in other neurodegenerative conditions including amyotrophic lateral sclerosis. 23 Relatively little is known about the genetics of spinocerebellar degenerations in the Sudanese population.…”
Section: Introductionmentioning
confidence: 99%
“…Autosomal Recessive Spastic Ataxia of Charlevoix Saguenay (ARSACS) (OMIM phenotype #270550) shows a challenging phenotypic overlap with HSP and HA, with a remarkable clinical diversity. [20][21][22] ALS2 (Alsin) (OMIM gene *606352) is another prominent example of a gene implicated in pyramidal syndromes, with overlapping roles in other neurodegenerative conditions including amyotrophic lateral sclerosis. 23 Relatively little is known about the genetics of spinocerebellar degenerations in the Sudanese population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent descriptions of ARSACS outside Québec also reported normal retinal fibres [7,10]. Neuropathy usually presents after the 2 nd decade of life and progresses to spastic paraparesis; [9] in that case, the authors highlight the early onset of neuropathy, with rapidly progressive distal weakness, resulting in loss autonomous gait.…”
Section: Discussionmentioning
confidence: 87%
“…In a study of 164 alleles of patients with ARSACS born in Québec, Richter et al (1999) reported that 92.6% cases were homozygous for the 6594 deletion [20]. Since the discovery of the gene responsible for ARSACS, more than 100 disease-causing genetic variants have been described around the world [7,10,12,21]. The authors present a case of a novel mutation related to ARSACS, in a Portuguese child.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations